Bedside Teaching in Undergraduate Surgical Education: A Pilot Study of Students’ Perspective - Alfehaid, Mohammed (Lietuvos chirurgija, 2024)
Background. Bedside teaching is an important tool in medical education. In recent years, studies have shown that this tool has witnessed gradual deterioration due to various reasons. Hence this pilot study was conducted to assess the students’ perspective about this tool and suggest remedies for the deficiencies. Methodology. An anonymous questionnaire was designed and students were requested to register the response offline. Data was analysed and inferences made. Results. Various deficiencies were highlighted by the students that require correction and improvement. Unavailability of suitable patients is a significant barrier. Communication skills and understanding of infection control protocols had got improved in 84% and 94% students respectively. Half of the students were fully satisfied or satisfied with the overall conduct of the bedside teaching and the other half were either partially satisfied or dissatisfied. Conclusion. There is a need to improve bedside teaching in Undergraduate Surgery course. Simulation sessions need to be devised and enhanced. Faculty development sessions to train the teachers are required.